Karakteristik Pengujian Tegangan Tembus Isolasi Gas Nitrogen Dan Karbon Dioksida Menggunakan Tegangan Tembus Dc Polaritas Negatif - Chandra, Andre; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research is focus on the comparison of breakdown voltage between CO2 and N2. In this experiment, the condition of gas pressures were at 1 bar, 2 bar, 3 bar and 4 bar respectively. Configuration of the choosen electrodes were needles and spheres electrodes. Breakdown voltage value for both gases were proportional with gas pressure. It showns that the breakdown voltage of N2 is higher than CO2 on the gas pressure condition 4 bar and gap of needles electrodes 1 cm. The same thing is shown by condition on the gap of spheres electrodes 1 cm and gas pressure 4 bar, whereas breakdown voltage of N2 is also higher than CO2. The breakdown voltages value for the gap of spheres electrodes 1 cm and gas pressure 4 bar reaches the highest value at 137.07 kV/cm and 121.49 kV/cm for N2 and CO2 respectively. This research also varies gas pressure and gap between electrodes. It showns that the breakdown voltage of N2 is also higher than CO2 for all conditions.Keywords— DC Negative Polarity, Electrodes, Isolator, CO2, N2, Breakdown Voltage